![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
因式分解(1)4a3b2-12a2b(2)-a3+15ab2-9ac2(3)m2(m-1)-4(1-m)2(4)(x2+4)2-16x2
因式分解(1)4a3b2-12a2b(2)-a3+15ab2-9ac2(3)m2(m-1)-4(1-m)2(4)(x2+4)2-16x2....
因式分解(1)4a3b2-12a2b(2)-a3+15ab2-9ac2(3)m2(m-1)-4(1-m)2(4)(x2+4)2-16x2.
展开
展开全部
(1)4a3b2-12a2b=4a2b (ab-3);
(2)-a3+15ab2-9ac2
=-a(a2-15b2+9c2);
(3)m2(m-1)-4(1-m)2
=m2(m-1)-4(m-1)2,
=(m-1)(m2-4m+4)
=(m-1)(m-2)2;
(4)(x2+4)2-16x2
=(x2+4-4x)(x2+4+4x)
=(x-2)2(x+2)2.
(2)-a3+15ab2-9ac2
=-a(a2-15b2+9c2);
(3)m2(m-1)-4(1-m)2
=m2(m-1)-4(m-1)2,
=(m-1)(m2-4m+4)
=(m-1)(m-2)2;
(4)(x2+4)2-16x2
=(x2+4-4x)(x2+4+4x)
=(x-2)2(x+2)2.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询